Shaping Character Education: Exploring the 'Dansaa' Program's Management in Early Childhood Educational Institutions - Saepudin, Saepudin; Rozi, Fathor; Qomariyah, Silfiyah Nur; Maghfiroh, Aniq Syahriyatul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the management of strengthening character education through the